2017
DOI: 10.1016/j.brainres.2016.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine produces long-term increases in cocaine reinforcement in adolescent but not adult rats

Abstract: Studies have shown that many smokers begin using nicotine during adolescence, yet the influence of early nicotine use on the response to other drugs of abuse in adulthood is not fully understood. In the current study, nicotine was administered to adolescent and adult rats for seven days. Thirty days later, cocaine-induced locomotor activity and cocaine self-administration were examined when the rats pretreated as adolescents were adults. Rats exposed to nicotine during early adolescence were sensitized thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(45 reference statements)
1
14
1
Order By: Relevance
“…In a more recent study, Pomfrey et al (2015) found no differences in cocaine self-administration between adult male rats that were pretreated with nicotine or vehicle in adolescence. In contrast to the results of Pomfrey et al (2015), Reed and Izenwasser (2017) found that nicotine preexposure in adolescence, but not in adulthood, increased rates of cocaine self-administration in male rats after a 30-day nicotine-free period. These studies used rates of cocaine self-administration on fixed- or progressive-ratio schedules as the dependent measure.…”
Section: Introductioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In a more recent study, Pomfrey et al (2015) found no differences in cocaine self-administration between adult male rats that were pretreated with nicotine or vehicle in adolescence. In contrast to the results of Pomfrey et al (2015), Reed and Izenwasser (2017) found that nicotine preexposure in adolescence, but not in adulthood, increased rates of cocaine self-administration in male rats after a 30-day nicotine-free period. These studies used rates of cocaine self-administration on fixed- or progressive-ratio schedules as the dependent measure.…”
Section: Introductioncontrasting
confidence: 93%
“…Pomfrey et al (2015), who found no effect of nicotine pretreatment on cocaine taking, injected rats with nicotine on post-natal day (PND) 28 until PND 43, and tested for cocaine self-administration beginning on PND 81–85. Reed and Izenwasser (2017) used a procedure similar to that of Pomfrey et al (i.e., rats had a 30-day drug-free period between nicotine preexposure and the beginning of cocaine self-administration), but found that nicotine preexposure increased cocaine self-administration in rats that were preexposed in adolescence, but not adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We are particularly cautious with regard to the generality of our findings to heroin and prescription opioids, because there are many differences between the neurobiological mechanisms of opioids and psychostimulants, and the risk factors and environmental conditions that control addiction to these drug classes (Badiani, 2013;Badiani et al, 2011;Caprioli et al, 2009). In addition, there is evidence that prior exposure to nicotine during adolescence increases cocaine selfadministration (Reed and Izenwasser, 2016) and amphetamine self-administration and reinstatement (Cortright et al, 2012).…”
Section: Methodological and Conceptual Considerationsmentioning
confidence: 89%
“…46 Adolescent research and animal studies confirm the ‘gateway to illicit drugs’ hypothesis that suggests the introduction of tobacco at an early age increases the likelihood of future illicit drug use. 47–49 Moreover, epidemiological research on addiction reveals better treatment and recovery outcomes for polysubstance users that quit tobacco use in comparison to counterparts that continue to smoke tobacco. 50–52 The potential for tobacco use reduction and quitting to lead to the reduction and quitting of other polysubstance use (as seen in PROMPT participants) is thus neurobiologically plausible.…”
Section: Discussionmentioning
confidence: 99%